(untitled) (Scientific journal of the Fergana State University, 2024)
This article explores the historical perspectives of gratitude within the framework of early world religions and philosophical views. It explains how the ideas of gratitude are expressed from the cultural and religious point of view of Uzbekistan, their importance and influence. In particular, one of the similarities in religious teachings and different religions is that they should make a person grateful for good and bad events and blessings, and also patiently wait for better days. Scientists say that people’s faith in religion gives them strength and confidence to live again and again. In this article, there are thoughts and opinions about the feeling of gratitude in people and the history of the formation of these ideas, based on religious and philosophical views.